Monitoring of Lung Ultrasound Acquisition using Volume Sweep Imaging Protocol - Guevara, N.; Montoya, X.; Alarcón, R.; Castañeda, B.; Romero Gutierrez, S.E. (SPIE, 2023)
The lung is vulnerable to suffering from different diseases, for its diagnosis one of the imaging technologies is ultrasound; however, it requires an expert to perform the acquisition and interpretation of the same. In Peru, many rural areas have little technology and untrained personnel, so one solution is to divide the acquisition and diagnosis. In this way, the radiologist only receives the video and performs the diagnosis through it and the local personnel is trained to perform the Volume Sweep Imaging protocol; however, there are some mistakes during its performance which are detected lately. To solve this problem, the paper proposes the use of three different algorithms: Adaptive Threshold, Threshold + non-consecutive minimum distance analysis and Derivative Analysis + Peak Detection, which show a better accuracy in the longitudinal direction of 77.96%; nevertheless, their work principle needs to be reformulated for transverse acquisition, where accuracy is less than 50%. This result show is possible to validate the protocol for lung ultrasound and give feedback to the locally trained physicians.
Keywords: Protocol (science); Computer science; Lung ultrasound; Ultrasound; Volume (thermodynamics); Data acquisition; Computer vision; Medical physics; Artificial intelligence; Radiology; Real-time computing; Medicine; Pathology; https://purl.org/pe-repo/ocde/ford#3.01.00